Ultrasound in hand and wrist: approach for a standardized examination - Harhaus-Wähner, Leila; Kotsougiani-Fischer, Dimitra; Hirche, Christoph; Lehnhardt, Marcus (Expert review of medical devices, 2014)
New very high-frequency ultrasound probes allow highly detailed imaging of superficial structures and thus are especially suitable for examination of the hand. For successful application, specific knowledge and experience as well as standardized examination techniques are required. Based on 11 determined sections of the flexor and extensor side of the hand, the authors present one approach to a standardized ultrasound examination allowing a quick view of all structures. An additional presentation of the most typical traumatic and degenerative disease patterns underlines the potency of this examination technique. With adequate equipment, training and expertise, ultrasound should be regarded as the first-line imaging modality for the assessment of a wide range of pathological conditions affecting the wrist and hand. An exact knowledge of the anatomical relation of the structures to each other gained from ultrasound experience is equally useful for following surgery of the cases.
published online: 09 Jan 2014
Gesehen am 25.03.2021